Evaluasi Pelaksanaan Program Indonesia Sehat dengan Pendekatan Keluarga pada Indikator TB Paru di Puskesmas Tayu II Kabupaten Pati - Naily Rahma Sari; Chriswardani Suryawati; Nurhasmadiar Nandini (Jurnal Kesehatan Masyarakat, 2019)
Tayu II Primary Health Care is one of the health center that has re-recorded data collection on PIS-PK in 2018. During the implementation there has never been an evaluation. Based on the data, there were differences between target achieved in PIS-PK and SPM. This study aims to evaluate the implementation of PIS-PK on the indicators of pulmonary TB in Tayu II Primary Health Care, Pati Regency. This was qualitative research with a descriptive approach. This research used in-depth interview  and observation method to collect data from sample selected based on purposive sampling technique. The variables studied are input, process, and environment. The results showed that the data collection hasn’t been accompanied by a supporting form for screening and referral because there was no work procedure used as a reference for implementing TB services in the PIS-PK program. In its implementation, there were no planning documents which cover data collection activities until further interventions that integrated with the P2TB program. While activities that have been carried out other than data collection were the provision of initial interventions, advising patients to go to the Tayu II Primary Health Care, and reporting. Reporting was still not optimal because there was no coordination forum. Tayu II Primary Health Care advised to develop and establish SOPs so that they can improve the quality of data collection on PIS-PK in TB case finding, construct policies that clarify the involvement of the P2TB program, and optimize coordination of internal networks for further intervention.  Keywords : Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK), TB Paru, Primary Health Care